Identification of Sola l 4 as Bet v 1 homologous pathogenesis related‐10 allergen in tomato fruits. Issue 3 (8th February 2014) - Wangorsch, Andrea; Jamin, Annette; Foetisch, Kay; Malczyk, Anna; Reuter, Andreas; Vierecke, Sabine; Schülke, Stefan; Bartel, Detlef; Mahler, Vera; Lidholm, Jonas; Vieths, Stefan; Scheurer, Stephan
<x xml:space="preserve">Abstract</x> Scope The aim was to investigate the potential contribution of a major birch pollen Bet v 1‐homologous allergen to birch pollen‐associated tomato fruit allergy. Methods and results Two isoforms of a Bet v 1‐homologous protein (designated Sola l 4) from tomato fruit were identified by cDNA‐cloning and produced as recombinant proteins. Allergen‐specific IgE levels to tomato, birch pollen, Bet v 1, and Sola l 4 were determined in birch pollen allergic patients with allergy or tolerance to tomato. Sola l 4 was recognized in 76% of birch/tomato allergic patients, while tomato‐ and Bet v 1‐specific IgE was detectable in 64% and 81% of sera. Almost all patients sensitized to Bet v 1 reacted with Sola l 4. Both Sola l 4 isoforms displayed allergenic potency and IgE‐cross‐reactivity with Bet v 1 as investigated by competitive ELISA and in vitro mediator release assay. Nevertheless, the reactivity pattern of patients' sera was diverse. Conclusion Sola l 4, a novel pathogenesis related‐10 protein, qualifies as major allergen in tomato fruits. Data suggest Sola l 4 as class II allergen. IgE‐testing using Sola l 4 showed low clinical specificity, but high sensitivity in tomato allergic patients and will further improve component‐resolved allergy diagnosis.